Surgical Management of Vascular Complications in Intravenous Drug Abusers: Experience at the National Institute of Cardiovascular Diseases (NICVD), Bangladesh - Bashar, AHM; Sabah, MN; Hossain, MF; Azad, QA; Alam, QM; Hossain, GMM; Hakim, E; Bhuiyan, MW; Rahman, MM; Alam, SAN; et al. (Cardiovascular Journal, 2010)
Background: Intravenous drug abuse (IVDA) is a global health care problem that has tremendous socio-economic implications. Vascular complications following IVDA are not uncommon and may have serious consequences. At the National Institute of Cardiovascular Diseases (NICVD), Dhaka, Bangladesh, there has been a steady increase in the number of cases with vascular complications of IVDA in the recent years. Objectives: The present study was undertaken to evaluate our surgical strategy for the management of various vascular complications following IVDA. Materials and Methods: Over the last 5 years, a total of 45 patients presented at the NICVD with various complications of IVDA. Thirty seven patients presented at the emergency department with bleeding from ruptured aneurysm or with impending aneurysm rupture. The remaining 8 patients presented at the vascular outpatient with deep venous thrombosis, superficial thrombophlebitis and chronic venous insufficiency. After resuscitation when necessary, excision of aneurysm was done either with simple ligation of the artery (Group A) or with restoration of arterial continuity (Group B). Outcome in the two groups were compared against the following parameters; acute limb ischemia, chronic limb ischemia, wound infection and lymphorrhoea. Results: There was no in-hospital mortality in this series. Both ligation and restoration of arterial continuity following aneurysmectomy were effective in treating the bleeding aneurysm. However, statistically significant differences were seen between the two groups in terms of acute and chronic limb ischemia. Restoration of arterial continuity was more effective in preventing acute and chronic limb ischemia. Conclusions: In Bangladesh, the incidence of IVDA with vascular complications is increasing at an alarming rate. In patients presenting with arterial pseudoaneurysms, surgical management should be aimed at restoration of arterial continuity whenever feasible. Key words: Intravenous drug abuse, Vascular complication, Aneurysm. DOI: 10.3329/cardio.v3i1.6426 Cardiovasc. j. 2010; 3(1): 45-49